The origin of the maximal lactate steady state (MLSS) - Hermann Heck; Henning Wackerhage (BMC, 2024)
Abstract The maximal lactate steady state, abbreviated as MLSS, is the maximal exercise intensity where the concentration of earlobe capillary or arterial blood lactate remains constant over time. In the late 1970s and early 1980s, we (i.e. Hermann Heck and co-workers) developed a direct test to determine the MLSS to investigate whether it occurred at a lactate concentration of 4 mmol.L− 1, as earlier predicted by Alois Mader and colleagues. The test consisted of each participant performing several constant-intensity running bouts of ≈ 30 min at intensities close to the estimated MLSS. During each run, we measured lactate every 5 min. Based on the results, we defined the MLSS as the "workload where the concentration of blood lactate does not increase more than 1 mmo.L − 1 during the last 20 min of a constant load exercise". This MLSS protocol is impractical for performance testing as it requires too many exercise bouts, but it is a gold standard to determine the real MLSS. It is especially useful to validate indirect tests that seek to estimate the MLSS.